Enhancing Students’ Critical Thinking, Creativity, and Mathematical Self-Esteem Through Worked-Example Learning With Culturally Responsive Pedagogy - Alamsyah, Trian Pamungkas; Rohimah, Siti Maryam (Program Studi Tadris Matematika dan Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Universitas Islam Negeri (UIN) Datokarama Palu, 2025)
This study aims to examine the impact of worked-example learning integrated with Culturally Responsive Pedagogy (CRP) on enhancing students’ critical thinking, creativity, and mathematical self-esteem. The research design employed was quasi-experimental, involving two groups of students: a control group that received conventional instruction and an experimental group that experienced the worked-example method based on Culturally Responsive Pedagogy. The participants in this study is 20 students of Natural Sciences Education program at Sultan Ageng Tirtayasa University during the first semester. Tests and questionnaires were used to gather data, and independent sample t-tests were used to compare the mean scores of the various groups. The worked-example method provides structured problem-solving examples to help students learn solution steps, while the CRP approach offers a culturally relevant learning environment and encourages students’ emotional engagement. Results indicated that students in the experimental group achieved higher averages in critical thinking, creativity, and mathematical self-esteem compared to those in the control group. These findings suggest that the combination of the worked-example method and Culturally Responsive Pedagogy effectively enhances students’ critical and creative thinking skills and fosters positive mathematical self-esteem. Moreover, this approach has been shown to make mathematics learning more inclusive and meaningful for students from diverse cultural backgrounds. This study contributes to mathematics education by proposing a learning strategy that not only supports cognitive development but also prioritizes cultural inclusivity, thereby promoting students’ academic success and personal growth